Former le politique, créer des références paysagères citoyennes - Caroline Guittet; Nolwenn Invernizzi (Projets de Paysage)
With the evolution of public landscape policies over the last century the notion of the landscape is steeped in a strong social dimension. The supposed democratisation of the idea of the landscape raises the question of the reference made to the notion during citizen protests against development projects. At the same time, with the growth in visual studies and the new schools of thought emerging in English-speaking countries, images of landscapes are studied through their impacts on politicians and public policies. Based on three case studies in Brittany, the article shows that visual landscape representations in the collective memory, in public policies, and in landscape projects are inherited from the processes of landscape architecture of the late 19th century. The hypothesis put forward is that the notion of landscape is rarely addressed by politicians due to the lack of contemporary visual references concerning landscapes as living environments.